DIAGNÓSTICO DE HEMOGLOBINOPATIA RARA SC APÓS ANTIBIÓTICOTERAPIA EM AMBIENTE HOSPITALAR: RELATO DE CASO - Ferraz, Silvia Leticia do Nascimento e Silva; Ferreira, Maria Clara Machado de Carvalho; Vieira, José Felipe Pinheiro do Nascimento; Paz, Ilara Ferreira Ribeiro; Silva, Janyerson Dannys Pereira da; FERREIRA DE ARAÚJO, ÉVERTON JOSÉ (Jornal de Ciências da Saúde do Hospital Universitário da Universidade Federal do Piauí, 2023)
SC Hemoglobinopathy is the result of heterozygous inheritance of the HbS and HbC alleles and can be the cause of anemic episodes. Under certain circumstances, the use of drugs may induce anemia as in membranopathies, erythroenzymopathies or in hemoglobinopathies. The present study reports the case of a 52 year old patient with infection at a surgical site after cervical arthrodesis following a C6 cervical spine fracture. The patient developed severe anemia (hemoglobin 5.8 g/dL) after administration of vancomycin and cefepime. After high performance liquid chromatography, it was elucidated that the patient was a carrier of hemoglobin SC. The use of antimicrobials showed a correlation with anemia, indicating the relevance of the rational use of drugs and the appropriate correlation between clinical and test results, especially in hospital settings.